Patai's Chemistry of Functional Groups 2018
DOI: 10.1002/9780470682531.pat0952
|View full text |Cite
|
Sign up to set email alerts
|

OxidativeCCBond Formation (Couplings, Cyclizations, Cyclopropanation, etc.)

Abstract: Oxidative coupling that can directly convert CH group for chemical transformations is, in theory, an ideal strategy in organic synthesis as it reduces the number of synthetic steps and possible by‐products. Hypervalent iodine reagent has become one of the most promising tools in developing oxidative coupling due to its unique reactivity similar to metal oxidants. We have pioneered the metal‐free oxidative coupling chemistry using the hypervalent iodine reagents, that is, phenyliodine(III) diacetate (PIDA, PhI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 248 publications
0
4
0
Order By: Relevance
“…Hypervalent iodine­(III) compounds have attracted much attention as oxidants in organic synthesis, as they can be a replacement for transition metals with the advantage of having environmentally benign properties. Although iodine­(III) reagents are competent to conduct many organic transformations, addition of a Lewis acid such as BF 3 is often a prerequisite for a process to occur. For example, it has been shown that an iodine­(III) reagent in conjunction with BF 3 ·Et 2 O considerably accelerates the processes that yield λ 3 -diaryliodanes, olefin diacetoxylation, and a plethora of other products. In this context, Ochiai et al reported that alcohols can be selectively oxidized by hypervalent iodine­(III) compound 2 to aldehydes or ketones in the presence of BF 3 ·Et 2 O as the catalyst (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Hypervalent iodine­(III) compounds have attracted much attention as oxidants in organic synthesis, as they can be a replacement for transition metals with the advantage of having environmentally benign properties. Although iodine­(III) reagents are competent to conduct many organic transformations, addition of a Lewis acid such as BF 3 is often a prerequisite for a process to occur. For example, it has been shown that an iodine­(III) reagent in conjunction with BF 3 ·Et 2 O considerably accelerates the processes that yield λ 3 -diaryliodanes, olefin diacetoxylation, and a plethora of other products. In this context, Ochiai et al reported that alcohols can be selectively oxidized by hypervalent iodine­(III) compound 2 to aldehydes or ketones in the presence of BF 3 ·Et 2 O as the catalyst (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews and book chapters have outlined the use of hypervalent iodine in organic chemistry, especially in oxidative C-C bond formation of aryl ethers. [107][108][109][110] The examples shown below are not comprehensive but seek to show that these couplings can be broadly utilized, from phenol oligomers to some of the most difficult intramolecular cases. These examples also highlight some of the key advances in catalysis; namely, the use of rstrow transition metals, hypervalent iodine complexes, nitrite organocatalysts, and electrochemistry.…”
Section: C-c Couplings Involving Aryl Ethersmentioning
confidence: 99%
“…Over the past 30 years, a substantial progress has been made in the utilization of the methodology for the formation of C-C bonds mediated by hypervalent iodine compounds. [83][84][85][86] Here we highlight the examples of hypervalent iodine (III) derivatives implementation in the couplings of two heteroarenes.…”
Section: Hypervalent Derivatives Of Iodine (Iii)mentioning
confidence: 99%